Musikken i samfundet – samfundet i musikken? – Refleksioner omkring “Gyldendals Musikhistorie” - Bonde, Lars Ole; Hørlyk, Thorkil; Mortensen, Tore; Nielsen, Per Drud; Pedersen, Peder Kaj (Modspil, 1984)